Just Good Enough to Eat? Animals in Theological Ethics Approaches - Martin M. Lintner (Acta Universitatis Carolinae Theologica, 2023)
The way humans treat animals is ambivalent: we bury our pets in animal cemeteries, and we slaughter and eat others. Even though the use of animals and coexistence with them has shaped people’s lives since time immemorial, Theology has long misjudged the importance of a theological reflection on animals. This has also led to blind spots in theological ethics. In the meantime, there are not only important approaches to a theology that takes animals into account but also a range of approaches within Catholic moral theology has been developed that seek to do justice to the intrinsic value of animals. They require a profound change in the human-animal relationship in the light of the Christian faith and call for more humane treatment of animals. This article presents the most important of those approaches from the German-speaking region and attempts to show common concerns but also different figures of argumentation.